2008
DOI: 10.1509/jppm.27.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Direct-to-Consumer Marketing of Predictive Medical Genetic Tests: Assessment of Current Practices and Policy Recommendations

Abstract: This research reviews the current state of affairs in the fast-growing area of direct-to-consumer marketing of genetic tests. The authors identify the unique nature of genetic tests and the ensuing consumer vulnerability. They also present a comprehensive examination of the current legal environment and an empirical analysis of genetic testing companies' online marketing practices. On the basis of the analysis and review, they make a set of policy recommendations that consists of consumer education, physician … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…Most consumers have little experiential knowledge of molecular biology and genetics (Goddard et al 2007;Ten Eyck and Williment 2003), making the mass media and companies offering DTC genetic tests the primary sources of information for this subject (Liu and Pearson 2008). Time and Newsweek magazines have devoted numerous covers to the subject, typically framing it as a miracle technology that will revolutionize the practice of medicine (Caulfield 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most consumers have little experiential knowledge of molecular biology and genetics (Goddard et al 2007;Ten Eyck and Williment 2003), making the mass media and companies offering DTC genetic tests the primary sources of information for this subject (Liu and Pearson 2008). Time and Newsweek magazines have devoted numerous covers to the subject, typically framing it as a miracle technology that will revolutionize the practice of medicine (Caulfield 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Use of risk information to change behavior and prevent disease (prevention framing) is another common presentation of genetic information (Collins et al 2003). Studies of DTC genetic testing websites and DTC advertising of genetic tests have also found excessive use of empowerment framing (Bowen et al 2005;Gulcher and Stefansson 2010;Hall and Gartner 2009;Lee and Crawley 2009;Liu and Pearson 2008;Matloff and Caplan 2008;McGowan and Fishman 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of DTC genetic tests has highlighted problems concerning the quality management of genetic testing in general. DTC genetic testing has been discussed as an alarming phenomenon [21,24,25,27,37,38,39,40,41,42,43,44] with strong questions raised regarding its marketing. Discussing the validity of DTC genetic tests for personal diets (‘nutrigenomic tests’), Goddard et al [38] argue that ‘The uncertain analytic validity, clinical validity and clinical utility of direct-to-consumer nutrigenomic tests may result in unnecessary interventions and cost’.…”
Section: Discussionmentioning
confidence: 99%
“…However, this advertising practice does not come without controversy, as the issue of genetics and health care has spurred continual debate. Proponents of PGTs DTC advertising 1 claim increased awareness of these tests can encourage consumers to consult with physicians or genetic counselors to make well informed decisions about their genetic health care needs (Liu & Pearson, 2008). Proponents also argue that learning about the tests can help consumers take steps to minimize their disease risks, thereby optimizing their health (Krasner, 2003).…”
Section: Introductionmentioning
confidence: 99%